2011
DOI: 10.5187/jast.2011.53.6.541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary KocetinTMon Meat Quality of Hanwoo Loin

Abstract: This study was performed to determine the effects of dietary Kocetin TM on meat quality of Hanwoo (Korean native cattle) beef.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Cho et al (2010) reported the effectiveness of dietary quercetin on meat quality of goat. Kang et al (2011) also studied the effect of dietary quercetin of Hanwoo. Others have also reported using rats and pigs (Ameho et al, 2008;de Boer et al, 2005;Luehring et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cho et al (2010) reported the effectiveness of dietary quercetin on meat quality of goat. Kang et al (2011) also studied the effect of dietary quercetin of Hanwoo. Others have also reported using rats and pigs (Ameho et al, 2008;de Boer et al, 2005;Luehring et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, (65) found that both storage period and lamb diet, no mean pH variations are absorbed, staying constant during storage. Similarly, dietary quercetin had no effect on muscle pH in Hanwoo beef (66). Also, (51) indicated that thyme leaves feeding did not significantly affect (P ≥ 0.05) moisture and pH values.…”
Section: Meat Phmentioning
confidence: 99%
“…The pH of breast meat from NSBC and SBC was determined by the method of Kang, Kim [8] with some modifications. One gram of each sample was mixed with 9 mL of distilled water and homogenized with a vortex machine (VM-96B, Jeiotech, Daejeon, Korea) at 2,000 rpm for 30 seconds.…”
Section: Analysis Of Physicochemical Propertiesmentioning
confidence: 99%